Ayat-Ayat Spiritual Ekologi (Eco-Spirituality) dan Kontribusianya Pada Lingkungan Rawan Bencana Banjir (Studi Living Al-Qur’an) - Faisol Nasar bin Madi; Moh Barmawi (Islamika Inside: Jurnal Keislaman dan Humaniora, 2022)
North Jember is part of a mountainous area that is potentially disaster-prone. The year 2006 became a terrible historical momentum called a national disaster, thus closing the possibility of such a disaster happening again is a shared need. Religion, which contains all the teachings, becomes a very important material in instilling awareness of the care for the environment around them, because in it there are descriptions of human responsibility for the dishes that have been given by God in the form of the universe. Preserving, preserving, for the sake of the sustainability of their lives is a must. This article is a review of the results of research from the vulnerable areas of North Jember with the focus of the study, a) The role of religious leaders in instilling awareness of protecting the environment, b) understanding of religious leaders on ecological spiritual verses and their influence on people's lives. The method in this research is qualitative with a living al-Qur'an approach. The findings in this study, a) Religious leaders have an important role in controlling in instilling awareness of protecting the environment, b) Understanding of religious leaders about the Qur'an related to protecting the environment includes the prohibition of making damage, the impact of exploitation, and recommendations about protecting and preserving the environment.